PENGARUH BERMAIN SENI KRIYA DAN KECERDASAN VISUAL SPASIAL TERHADAP PEMAHAMAN GEOMETRI - Ilhami, Akmillah (JISPE Journal of Islamic Primary Education, 2021)
ABSTRACT The purposes of this research were to know the effect of playing art-crafts and visual-spatial intelligence toward children's geometry understanding of kindergarten B (average age of 5 until 6 years). The method in this research used experimental research with treatment design by level 2x2. The sample of this research were 120 students. The procedure of collecting data used stratified multistage cluster random sampling technique. Analysis data in this research used two-way ANOVA. The results of this research were: 1) The geometry understanding of children who given playing the art of origami craft has a higher impact than who playing the art of collage craft (Fhitung = 7,78 > Ftabel = 3,97); 2) There is an interaction effect between children that given playing art-crafts and visual-spatial intelligence toward their understanding of geometry (Fhitung = 14,15 > Ftabel = 3,97); 3) The geometry understanding of children who have high visual-spatial intelligence given playing the art of origami craft have a higher scores impact than children who given playing the art of collage craft (QhitungA1B1-A2B1 = 6,55 > Qtabel = 3,74); and 4) The geometry understanding of children who have low visual-spatial intelligence given playing the art of collage craft have a higher scores impact than children who given playing the art of origami craft (Qhitung A1B2-A2B2 = 0,97 < Qtabel = 3,74)).